Recombinant human chorionic gonadotropin induces signaling pathways towards cancer prevention in the breast of BRCA1/2 mutation carriers. Issue 2 (30th June 2022) - Su, Yanrong; Dang, Nhi M.; Depypere, Herman; Santucci-Pereira, Julia; Gutiérrez-Díez, Pedro J.; Kanefsky, Joice; Janssens, Jaak Ph.; Russo, Jose
Abstract : Background: Strategies for breast cancer prevention in women with germline BRCA1/2 mutations are limited. We previously showed that recombinant human chorionic gonadotropin (r-hCG) induces mammary gland differentiation and inhibits mammary tumorigenesis in rats. The present study investigated hCG-induced signaling pathways in the breast of young nulliparous women carrying germline BRCA1/2 mutations. Methods: We performed RNA-sequencing on breast tissues from 25 BRCA1/2 mutation carriers who received r-hCG treatment for 3 months in a phase II clinical trial, we analyzed the biological processes, reactome pathways, canonical pathways, and upstream regulators associated with genes differentially expressed after r-hCG treatment, and validated genes of interest. Results: We observed that r-hCG induces remarkable transcriptomic changes in the breast of BRCA1/2 carriers, especially in genes related to cell development, cell differentiation, cell cycle, apoptosis, DNA repair, chromatin remodeling, and G protein-coupled receptor signaling. We revealed that r-hCG inhibits Wnt/β-catenin signaling, MYC, HMGA1, and HOTAIR, whereas activates TGFB/TGFBR-SMAD2/3/4, BRCA1, TP53, and upregulates BRCA1 protein. Conclusion: Our data suggest that the use of r-hCG at young age may reduce the risk of breast cancer in BRCA1/2 carriers by inhibiting pathways associated with stem/progenitor cell maintenance and neoplastic transformation, whereas activating genes crucial for breast epithelial differentiation and lineage commitment, and DNA repair.